The Effect of Entertaining Program Using Some Artistic Gymnastics Skills to Reduce the Level of Aggressive in Children with Autism - Noor Essam Mohammed; Sanaria Jabbar Mahmoud; shaimaa Hasoon Mashkur (Zanco Journal of Humanity Sciences)
The aim of the current research is to identify the effect of the entertaining program and learn some basic skills of artistic gymnastics, which are the skill hand stand in artistic gymnastics, and to work on reducing the level of aggressive in children with autism. The two researchers used the experimental method, as they divided the study sample into two homogeneous groups, control and experimental, for children with autism. They obtained high scores on the aggressive behavior scale, and the problem of the research emerged from the observation by the two researchers at the Friendship Center for Autism that the children did not learn any of the skills related to gymnastics, as they prepared special exercises to teach them the skill of standing on hands easily وThe research sample was chosen randomly by drawing a lottery into a regular sample consisting of (6) children for the control group and (6) children for the experimental group, and (6) children were excluded from them because they participated in the exploratory experiment. After completing the main experiment, the two researchers concluded that the prepared exercises had an effect. The experimental group was positive about learning the skill. The most important recommendations were the necessity of preparing special exercises to learn other skills in artistic gymnastics in all autism centers.